Preparation method of nano-wave absorbing material and its application in invisible speakers
By using raw materials such as zinc nitrate, lanthanum nitrate, nickel nitrate and cobalt nitrate in nano zinc oxide absorbing materials to prepare sols, and coated metal soft magnetic powders, the problem of insufficient impedance matching ability of nano zinc oxide nanoabsorbing materials is solved, and a significantly improved low-frequency absorbing performance is achieved.
Patent Information
- Application Number
- CN202410898027.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-05
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-07-05
AI Technical Summary
The impedance matching capability of existing nano zinc oxide nanoabsorbent materials is not ideal enough, resulting in insufficient low-frequency absorption performance.
The first sol is prepared by raw materials including zinc nitrate and lanthanum nitrate, and the second sol is prepared by raw materials including nickel nitrate and cobalt nitrate. The metal soft magnetic powder is successively coated to obtain a nano-absorbent material.
By optimizing the impedance matching performance of the absorbing material, its low-frequency absorbing performance is significantly improved, which significantly improves the absorption peak and effective bandwidth of the nano-absorbing material.
Smart Images

Figure CN118711972B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of chemical materials, and in particular to a preparation method of a nanometer wave-absorbing material and an application thereof in a stealth speaker. Background Art
[0002] Stealth technology is an interdisciplinary and comprehensive technology that involves multiple disciplines such as structure, materials, optics, electricity, aerodynamics, etc. Stealth technology, also known as "low detectable technology", refers to the technology that minimizes the detection system's ability to detect and identify targets by weakening the radar, infrared, acoustic and optical signal characteristics that indicate the presence of the target.
[0003] When reducing the target radar signature, using shape stealth is effective. The following principles should be followed when adopting radar shape stealth design: avoid any interface that intersects vertically with edges, corners, tips, notches, etc. to eliminate the corner reflector effect; avoid large planes, use edge diffraction instead of mirror reflection to eliminate mirror reflection light surfaces; reduce flight storage to reduce the reflection cross section of radar waves; reasonably design the engine intake and exhaust systems, and use flush inlets; eliminate exposed protrusions to make the fuselage form a smooth transition curve.
[0004] Stealth has the advantages of wide application range, significant effect and stronger applicability to high-frequency radar, but it will also have adverse effects on other performances such as the aerodynamic performance of the aircraft, structural stress and radar heat dissipation in other directions. Therefore, it is also necessary to use radar absorbing stealth materials for stealth.
[0005] Radar absorbing stealth materials refer to materials that can reduce the target radar scattering cross section through their own absorption, making it difficult for them to recover satisfactory echoes for radar detection, thereby achieving stealth. Radar absorbing materials are used for military stealth only in a small proportion, and their civilian market is much broader. Radar absorbing materials can be used to improve electromagnetic compatibility, RFID antenna anti-metal isolation, safety protection and many other aspects, involving communications, textiles, power equipment and other industries.
[0006] When a beam of electromagnetic waves is incident on the surface of an absorbing material, three types of signals are usually generated: one is that the electromagnetic waves are reflected on the surface of the absorbing material; the second is that they are absorbed inside the material; and the third is that they pass through the absorbing material. Part of the incident electromagnetic waves will be reflected on the surface of the absorbing material, and the unreflected part will enter the interior of the material. The electromagnetic waves incident into the interior of the material are lost due to the dielectric loss or loss of the absorbing material, or are attenuated due to interference. The better the absorbing performance of the absorbing material, the more the electromagnetic waves incident into the material will be lost, thereby reducing the reflection and transmission of electromagnetic waves on the surface and inside, thereby achieving the purpose of electromagnetic stealth.
[0007] At present, radar absorbing materials are mainly composed of absorbents and polymer materials (such as resins, rubbers and their modified materials). Among them, the key to determining the quality of absorbing performance is the type and content of the selected absorbent.
[0008] According to the different absorption principles of absorbers, they can usually be divided into two categories: electric loss type and magnetic loss type. According to the structural form of absorbers, they can be divided into coating type and structural type. Absorbing coatings are formed by dispersing powder absorbers with specific dielectric parameters in a matrix. Structural absorbers are a kind of multifunctional reinforced plastics that can be used as structural parts and have the advantages of composite materials being light in weight. At the same time, they can absorb or transmit electromagnetic waves. They are currently receiving extensive research and attention.
[0009] Nano absorber materials refer to materials whose characteristic dimensions are in the nanometer range (1-100nm). Nano materials not only have good absorbing effects, but also have the characteristics of good broadband compatibility, light weight, thin thickness, and good mechanical properties.
[0010] There are currently three types of nanoparticles used in coatings: one is metal oxides: such as titanium oxide, aluminum oxide, iron oxide, zinc oxide, etc.; the second is nanometal powders, such as aluminum, titanium, neodymium, chromium, and molybdenum; the third is inorganic salts, such as calcium carbonate, layered silicates, and one-dimensional nano-scale clays.
[0011] Zinc oxide is a new type of multifunctional inorganic semiconductor material with direct band gap. The band gap is 3.37 eV at room temperature, the exciton binding energy is as high as 60 MeV, and it has good piezoelectric properties. It is widely used in ultraviolet light emitting materials, transparent conductive, field emission display devices, solar cells and gas sensing ultraviolet semiconductor optoelectronic device materials. In recent years, people have found that zinc oxide is a good wave absorbing material, which has aroused great interest. In addition, as a new type of multifunctional inorganic material, nano zinc oxide also has many excellent properties in acoustics, magnetism, light, electricity and other aspects. Therefore, with the deepening of research, nano zinc oxide may become a new generation of functional composite wave absorbing stealth material.
[0012] However, the technical problem of nano zinc oxide in the prior art is that its impedance matching capability is not ideal enough. Summary of the invention
[0013] One of the problems solved by the present invention is how to provide a nano zinc oxide type nano wave absorbing material with better impedance matching ability.
[0014] In order to solve at least one of the above problems, the present invention provides a method for preparing a nanometer absorbing material, the preparation method comprising:
[0015] S100, preparing a first sol using raw materials including zinc nitrate and lanthanum nitrate;
[0016] S200, preparing a second sol using raw materials including nickel nitrate and cobalt nitrate;
[0017] S300, using the first sol and the second sol in sequence to coat the metal soft magnetic powder to obtain a nano wave absorbing material.
[0018] In any of the above technical solutions, S100 specifically includes:
[0019] S110, uniformly mixing lanthanum nitrate, zinc nitrate and chitosan in water to obtain a first mixture;
[0020] S120, heating the first mixture to 96° C. to 98° C., adding polyvinyl alcohol to the first mixture, and stirring the mixture to obtain a second mixture;
[0021] S130, feeding the second mixture into a reactor, and performing a hydrothermal reaction for 2 h to 2.5 h at a temperature of 120° C. to 140° C. and a pressure of 4 MPa to 6 MPa to obtain a first sol.
[0022] In any of the above technical solutions, in S110, lanthanum nitrate, zinc nitrate and chitosan are uniformly mixed in water at a mass ratio of lanthanum nitrate: zinc nitrate: chitosan: water = (0.1-0.2): (2-4): (2-4): 100 to obtain a first mixture.
[0023] In any of the above technical solutions, in S120, polyvinyl alcohol is added to the first mixture at a mass ratio of polyvinyl alcohol: water = 80:100 according to the amount of water added in S110.
[0024] In any of the above technical solutions, S200 specifically includes:
[0025] S210, uniformly mixing nickel nitrate, cobalt nitrate and sodium alginate in water to obtain a third mixture;
[0026] S220, heating the third mixture to 40° C. to 50° C., adding polyvinyl alcohol to the third mixture, and stirring the mixture to obtain a fourth mixture;
[0027] S230, feeding the fourth mixture into a reactor, and performing a hydrothermal reaction for 2 h to 2.5 h at a temperature of 120° C. to 140° C. and a pressure of 4 MPa to 6 MPa to obtain a second sol.
[0028] In any of the above technical solutions, in S210, nickel nitrate, cobalt nitrate and sodium alginate are uniformly mixed in water at a mass ratio of nickel nitrate: cobalt nitrate: sodium alginate: water = (0.1-0.2): (0.2-0.4): (2-4): 100 to obtain a third mixture.
[0029] In any of the above technical solutions, in S220, polyvinyl alcohol is added to the third mixture at a mass ratio of polyvinyl alcohol: water = 80:100 according to the amount of water added in S210.
[0030] In any of the above technical solutions, the metal soft magnetic powder in S300 is Fe 90 Si 7 Cr 3 Metal soft magnetic powder.
[0031] In any of the above technical solutions, S300 specifically includes:
[0032] S310, mixing the metal soft magnetic powder and the first sol uniformly, and ball milling them in a ball mill using zirconium oxide as a grinding medium, and spraying 8 wt % to 12 wt % sodium hydroxide solution several times during the ball milling process until the pH value detection result reaches 9-10;
[0033] S320, adding the second sol into the ball mill and continuing the ball milling, spraying 8 wt % to 12 wt % sodium hydroxide solution several times during the ball milling process until the pH value detection result reaches 11-12;
[0034] S330, separating the solid, washing, filtering, drying, and calcining at a temperature of 680° C. to 720° C. for 3 h to 4 h to obtain a nano-absorbing material.
[0035] In any of the above technical solutions, in S310, the metal soft magnetic powder and the first sol are evenly mixed at a mass ratio of first sol: metal soft magnetic powder = (35-45):100; in S320, the second sol is added to the ball mill for further ball milling at a mass ratio of second sol: metal soft magnetic powder = (10-15):100.
[0036] The present invention also provides a stealth speaker, comprising a speaker box, a sound outlet hole being arranged at one end of the speaker box, a partition net being installed on the sound outlet hole, a plurality of honeycomb-shaped sound outlet mesh holes being arranged on the partition net, the surfaces of the speaker box and the partition net being covered with nano-wave absorbing material, and the nano-wave absorbing material being obtained by adopting the preparation method of the above-mentioned technical scheme.
[0037] Beneficial Effects
[0038] The preparation method of the present invention firstly uses raw materials including zinc nitrate and lanthanum nitrate to prepare a first sol; then uses raw materials including nickel nitrate and cobalt nitrate to prepare a second sol; finally, the first sol and the second sol are used in sequence to coat the metal soft magnetic powder to obtain the nano wave absorbing material. The metal soft magnetic powder can effectively optimize the impedance matching performance of the wave absorbing material and improve the low-frequency wave absorbing performance of the wave absorbing material. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a microscopic electron microscope image of the absorbing material prepared in Example 1 of the present invention;
[0040] Figure 2 This is a cross-sectional view of a loudspeaker according to Embodiment 3 of the present invention;
[0041] Figure 3 This is a front view of the speaker according to embodiment 3 of the present invention. DETAILED DESCRIPTION
[0042] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the following is a detailed description of the specific embodiments of the present invention.
[0043] Unless otherwise specified, the reagents and raw materials used in the present invention can be purchased through commercial channels. The experimental methods in the following examples without specifying specific conditions are selected according to conventional methods and conditions, or according to the product specifications.
[0044] An embodiment of the present invention provides a method for preparing a nanometer wave absorbing material, the method comprising:
[0045] S100, preparing a first sol using raw materials including zinc nitrate and lanthanum nitrate;
[0046] S200, preparing a second sol using raw materials including nickel nitrate and cobalt nitrate;
[0047] S300, using the first sol and the second sol in sequence to coat the metal soft magnetic powder to obtain a nano wave absorbing material.
[0048] The present invention uses metal soft magnetic powder and nano zinc oxide to prepare a composite wave absorbing material. The metal soft magnetic powder can effectively optimize the impedance matching performance of the wave absorbing material and improve the low-frequency wave absorbing performance of the wave absorbing material. Nickel cobalt oxide helps multiple reflections of electromagnetic waves, further improving the wave absorbing ability of the material.
[0049] In some implementations of the present invention, S100 specifically includes:
[0050] S110, uniformly mixing lanthanum nitrate, zinc nitrate and chitosan in water to obtain a first mixture;
[0051] S120, heating the first mixture to 96° C. to 98° C., adding polyvinyl alcohol to the first mixture, and stirring the mixture to obtain a second mixture;
[0052] S130, feeding the second mixture into a reactor, and performing a hydrothermal reaction for 2 h to 2.5 h at a temperature of 120° C. to 140° C. and a pressure of 4 MPa to 6 MPa to obtain a first sol.
[0053] Preferably, in S110, lanthanum nitrate, zinc nitrate and chitosan are uniformly mixed in water at a mass ratio of lanthanum nitrate: zinc nitrate: chitosan: water = (0.1-0.2): (2-4): (2-4): 100 to obtain a first mixture.
[0054] Further preferably, in S110, lanthanum nitrate, zinc nitrate and chitosan are uniformly mixed in water at a mass ratio of lanthanum nitrate: zinc nitrate: chitosan: water = 0.15:3:4:100 to obtain a first mixture.
[0055] Preferably, in S120, polyvinyl alcohol is added to the first mixture at a mass ratio of polyvinyl alcohol: water = 80:100 according to the amount of water added in S110.
[0056] In some implementations of the present invention, S200 specifically includes:
[0057] S210, uniformly mixing nickel nitrate, cobalt nitrate and sodium alginate in water to obtain a third mixture;
[0058] S220, heating the third mixture to 40° C. to 50° C., adding polyvinyl alcohol to the third mixture, and stirring the mixture to obtain a fourth mixture;
[0059] S230, feeding the fourth mixture into a reactor, and performing a hydrothermal reaction for 2 h to 2.5 h at a temperature of 120° C. to 140° C. and a pressure of 4 MPa to 6 MPa to obtain a second sol.
[0060] Preferably, in S210, nickel nitrate, cobalt nitrate and sodium alginate are uniformly mixed in water at a mass ratio of nickel nitrate:cobalt nitrate:sodium alginate:water=(0.1-0.2):(0.2-0.4):(2-4):100 to obtain a third mixture.
[0061] Further preferably, in S210, nickel nitrate, cobalt nitrate and sodium alginate are uniformly mixed in water at a mass ratio of nickel nitrate: cobalt nitrate: sodium alginate: water = 0.1:0.3:3:100 to obtain a third mixture.
[0062] Preferably, in S220, polyvinyl alcohol is added to the third mixture at a mass ratio of polyvinyl alcohol: water = 80:100 according to the amount of water added in S210.
[0063] The electrostatic attraction between chitosan and sodium alginate helps nickel salt and cobalt salt to be evenly coated on the surface of the metal soft magnetic powder, and promotes the uniform distribution of nickel, cobalt, zinc and lanthanum on the surface of the metal soft magnetic powder to ensure the impedance matching ability of the material.
[0064] In some embodiments of the present invention, the metal soft magnetic powder in S300 is Fe90Si7Cr3 metal soft magnetic powder.
[0065] In some implementations of the present invention, S300 specifically includes:
[0066] S310, mixing the metal soft magnetic powder and the first sol uniformly, and ball milling them in a ball mill using zirconium oxide as a grinding medium, and spraying 8 wt % to 12 wt % sodium hydroxide solution several times during the ball milling process until the pH value detection result reaches 9-10;
[0067] S320, adding the second sol into the ball mill and continuing the ball milling, spraying 8 wt % to 12 wt % sodium hydroxide solution several times during the ball milling process until the pH value detection result reaches 11-12;
[0068] S330, separating the solid, washing, filtering, drying, and calcining at a temperature of 680° C. to 720° C. for 3 h to 4 h to obtain a nano-absorbing material.
[0069] Preferably, in S310 , the metal soft magnetic powder and the first sol are uniformly mixed at a mass ratio of first sol:metal soft magnetic powder=(35-45):100.
[0070] Further preferably, in S310, the metal soft magnetic powder and the first sol are uniformly mixed at a mass ratio of first sol:metal soft magnetic powder=40:100.
[0071] Preferably, in S320, the second sol is added into a ball mill for further ball milling at a mass ratio of the second sol to the metallic soft magnetic powder of 12:100.
[0072] The above steps control the microstructure of the absorbing material by repeatedly adding alkali to dry grinding and utilizing the electrostatic attraction effect of sodium alginate and chitosan, so as to grow a kind of Figure 1 The uniform and dense flaky coating layer shown is formed, thereby obtaining a nano-wave absorbing material with uniform performance and uniform distribution of metal oxides on the surface of the metal soft magnetic powder.
[0073] This embodiment provides a method for preparing a nanometer wave absorbing material, which specifically includes the following steps:
[0074] S1. Evenly mix lanthanum nitrate, zinc nitrate and chitosan in water at a mass ratio of lanthanum nitrate: zinc nitrate: chitosan: water = 0.1:2:2:100 to obtain a first mixture;
[0075] S2, heating the first mixture to 98° C., adding polyvinyl alcohol to the first mixture at a mass ratio of polyvinyl alcohol: water = 80:100 according to the amount of water added in S1, and stirring evenly to obtain a second mixture;
[0076] S3, feeding the second mixture into a reactor, and performing a hydrothermal reaction for 2 hours at a temperature of 120° C. to 125° C. and a pressure of 4 MPa to 4.5 MPa to obtain a first sol;
[0077] S4, mixing nickel nitrate, cobalt nitrate and sodium alginate in water at a mass ratio of nickel nitrate: cobalt nitrate: sodium alginate: water = 0.1:0.4:2:100 to obtain a third mixture;
[0078] S5, heating the third mixture to 40° C., adding polyvinyl alcohol to the third mixture at a mass ratio of polyvinyl alcohol: water = 80:100 according to the amount of water added in S4, and stirring evenly to obtain a fourth mixture;
[0079] S6, feeding the fourth mixture into a reactor, and performing a hydrothermal reaction for 2 hours at a temperature of 135° C. to 140° C. and a pressure of 4 MPa to 4.5 MPa to obtain a second sol;
[0080] S7, mixing the soft magnetic powder and the first sol in a mass ratio of 40:100, and ball milling them in a ball mill using zirconium oxide as a grinding medium, spraying 8wt% sodium hydroxide solution several times during the ball milling process until the pH value reaches 9-10;
[0081] S8, adding the second sol to the ball mill according to the mass ratio of the second sol to the metal soft magnetic powder = 12:100, and continuing the ball milling, spraying 8wt% sodium hydroxide solution several times during the ball milling process until the pH value detection result reaches 11-12;
[0082] S9, separating the solid, washing, filtering, drying, and calcining at 700° C. for 3 h to obtain a nano-wave absorbing material.
[0083] The absorbing material of Example 1 achieved an absorption peak of -49 dB and an effective bandwidth of 4.6 GHz at a thickness of 2.69 mm.
[0084] This embodiment provides a method for preparing a nanometer wave absorbing material, which specifically includes the following steps:
[0085] S1. Evenly mix lanthanum nitrate, zinc nitrate and chitosan in water according to a mass ratio of lanthanum nitrate: zinc nitrate: chitosan: water = 0.2:4:4:100 to obtain a first mixture;
[0086] S2, heating the first mixture to 96° C., adding polyvinyl alcohol to the first mixture at a mass ratio of polyvinyl alcohol: water = 80:100 according to the amount of water added in S1, and stirring evenly to obtain a second mixture;
[0087] S3, feeding the second mixture into a reactor, and performing a hydrothermal reaction for 2 hours at a temperature of 120° C. to 125° C. and a pressure of 4 MPa to 4.5 MPa to obtain a first sol;
[0088] S4, mixing nickel nitrate, cobalt nitrate and sodium alginate in water at a mass ratio of nickel nitrate: cobalt nitrate: sodium alginate: water = 0.2:0.2:3:100 to obtain a third mixture;
[0089] S5, heating the third mixture to 40° C., adding polyvinyl alcohol to the third mixture at a mass ratio of polyvinyl alcohol: water = 80:100 according to the amount of water added in S4, and stirring evenly to obtain a fourth mixture;
[0090] S6, feeding the fourth mixture into a reactor, and performing a hydrothermal reaction for 2 hours at a temperature of 135° C. to 140° C. and a pressure of 4 MPa to 4.5 MPa to obtain a second sol;
[0091] S7, mixing the soft magnetic powder and the first sol in a mass ratio of 40:100, and ball milling them in a ball mill using zirconium oxide as a grinding medium, spraying 8wt% sodium hydroxide solution several times during the ball milling process until the pH value reaches 9-10;
[0092] S8, adding the second sol to the ball mill according to the mass ratio of the second sol to the metal soft magnetic powder = 10:100, and continuing to ball mill, spraying 8wt% sodium hydroxide solution several times during the ball milling process until the pH value detection result reaches 11-12;
[0093] S9, separating the solid, washing, filtering, drying, and calcining at 680° C. for 4 h to obtain a nano-absorbing material.
[0094] The absorbing material of Example 2 achieved an absorption peak of -48 dB and an effective bandwidth of 4.7 GHz at a thickness of 2.69 mm.
[0095] The present embodiment provides a stealth speaker, including a speaker box 1, a sound outlet hole is arranged at one end of the speaker box 1, a partition net 2 is installed on the sound outlet hole, a plurality of honeycomb-shaped sound outlet mesh holes are arranged on the partition net 2, and the surfaces of the speaker box 1 and the partition net 2 are covered with the nano-absorbing material as described in the above embodiment, which can effectively improve the overall absorbing ability of the speaker.
[0096] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.
Claims
1. A method for preparing a nanometer absorbing material, characterized in that: The preparation method comprises: S100, preparing a first sol using raw materials including zinc nitrate and lanthanum nitrate; S200, preparing a second sol using raw materials including nickel nitrate and cobalt nitrate; S300, using the first sol and the second sol in sequence to coat the metal soft magnetic powder to obtain the nano wave absorbing material, wherein the metal soft magnetic powder is Fe 90 Si7Cr3 metal soft magnetic powder; The step S300 specifically includes: S310, mixing the metal soft magnetic powder and the first sol uniformly, and ball milling them in a ball mill using zirconium oxide as a grinding medium, and spraying 8 wt % to 12 wt % sodium hydroxide solution multiple times during the ball milling process until the pH value detection result reaches 9-10; S320, adding the second sol into a ball mill and continuing ball milling, spraying 8 wt % to 12 wt % sodium hydroxide solution several times during the ball milling process until the pH value detection result reaches 11-12; S330, separating the solid, washing, filtering, drying, and calcining at a temperature of 680° C. to 720° C. for 3 h to 4 h to obtain the nano-wave absorbing material.
2. The preparation method according to claim 1, characterized in that: S100 specifically includes: S110, uniformly mixing lanthanum nitrate, zinc nitrate and chitosan in water to obtain a first mixture; S120, heating the first mixture to 96° C. to 98° C., adding polyvinyl alcohol to the first mixture, and stirring the mixture to obtain a second mixture; S130, feeding the second mixture into a reactor, and performing a hydrothermal reaction for 2 h to 2.5 h at a temperature of 120° C. to 140° C. and a pressure of 4 MPa to 6 MPa to obtain the first sol.
3. The preparation method according to claim 2, characterized in that: In S110, the lanthanum nitrate, the zinc nitrate and the chitosan are uniformly mixed in water at a mass ratio of lanthanum nitrate: zinc nitrate: chitosan: water = (0.1-0.2): (2-4): (2-4): 100 to obtain the first mixture.
4. The preparation method according to claim 2, characterized in that: In S120, the polyvinyl alcohol is added to the first mixture at a mass ratio of polyvinyl alcohol: water = 80:100 according to the amount of water added in S110.
5. The preparation method according to claim 1, characterized in that: S200 specifically includes: S210, uniformly mixing nickel nitrate, cobalt nitrate and sodium alginate in water to obtain a third mixture; S220, heating the third mixture to 40° C. to 50° C., adding polyvinyl alcohol to the third mixture, and stirring the mixture to obtain a fourth mixture; S230, feeding the fourth mixture into a reactor, and performing a hydrothermal reaction for 2 h to 2.5 h at a temperature of 120° C. to 140° C. and a pressure of 4 MPa to 6 MPa to obtain the second sol.
6. The preparation method according to claim 5, characterized in that: In S210, the nickel nitrate, the cobalt nitrate and the sodium alginate are uniformly mixed in water according to a mass ratio of nickel nitrate:cobalt nitrate:sodium alginate:water=(0.1-0.2):(0.2-0.4):(2-4):100 to obtain the third mixture; In S220, polyvinyl alcohol is added to the third mixture at a mass ratio of polyvinyl alcohol: water = 80:100 according to the amount of water added in S210.
7. The preparation method according to claim 1, characterized in that: In S310, the metal soft magnetic powder and the first sol are uniformly mixed at a mass ratio of first sol:metal soft magnetic powder=(35-45):100; in S320, the second sol is added into the ball mill for further ball milling at a mass ratio of second sol:metal soft magnetic powder=(10-15):
100.
8. A stealth speaker, characterized in that: The speaker box (1) comprises a speaker box (1), one end of which is provided with a sound outlet, a partition net (2) is installed on the sound outlet, a plurality of honeycomb-shaped sound outlet mesh holes are provided on the partition net (2), and the surfaces of the speaker box (1) and the partition net (2) are covered with a nano-wave absorbing material obtained by the method for preparing a nano-wave absorbing material according to any one of claims 1 to 7.
Citation Information
Patent Citations
Nickel-zinc-magnesium-lanthanum ferrite nano wave-absorbing material and preparation method thereof
CN102531563A
Insulation coating method for magnetically soft alloy powder
CN115394552A